Rennyo and the roots of modern Japanese Buddhism - Blum, Mark Laurence; Yasutomi, Shin'ya, 1944-2017 (Oxford University Press, 2006)
Rennyo Shonin (1415-1499) is considered the "second founder" of Shin Buddhism. Under his leadership, the Honganji branch grew in size and power, becoming a national organization with great wealth and influence. Rennyo's success lay in conveying an attractive spiritual message while exerting effective administrative control. A savvy politician as well as religious leader, ennyo played a significant role in political, economic, and institutional developments. Though he is undeniably one of the most influential persons in the history of Japanese religion, his legacy remains enigmatic an